Organic Terahertz Generators with Wide Entire-Molecular Phonon-Free Range and Their Application in Broadband Terahertz Spectroscopy - Lee, Yun Sang; Kim, Chaeyoon; Jungkwon, O. H.; Yoon, Woojin; Yun, Hoseop; Jazbinsek, Mojca; Rotermund, Fabian; Kwon, O. Pil (Small Structures, 2025)
New organic nonlinear optical crystals with a broad range free from strong molecular phonon vibrations have been developed for dimple-free THz wave generation. The newly designed 7-fluoro-2-(4-hydroxy-3-methylstyryl)-1-methylquinolin-1-ium (OM7FQ) crystals exhibiting an optimal order parameter feature a unique orthogonal cation–anion dipole coupling, in contrast to the parallel cation–anion dipole coupling found in benchmark organic crystals. The introduction of a fluoro substituent on the cationic electron acceptor, compared to nonfluorinated analogs, results in the additional formation of stronger cation–anion and cation–cation interactions, leading to increased crystal density and reduced void volume. OM7FQ single crystals exhibit a broad phonon-free range from 0.9 to 2.3 THz, defined by an absorption coefficient ≤15 mm−1. This leads to efficient, dimple-free THz wave generation with a dimple-free flat spectral band spanning 0.5–2.7 THz when pumped at the technically significant wavelength of 800 nm. Additionally, OM7FQ crystals produce THz electric fields 3.6 times higher than analogous nonfluorinated benchmark crystals with parallel cation–anion dipole coupling. The application of OM7FQ crystals in broadband THz spectroscopy has been successfully demonstrated for sensing biologically important lactose in commercial infant formulas.
Keywords: nonlinear optics; organic crystals; terahertz spectroscopy; terahertz waves